A Community-Based Disaster Preparedness-Based Catastrophic Emergency Management Model at Grandmed Lubuk Pakam Hospital in 2023 - Ganda Impola (Institut Kesehatan Medistra Lubuk Pakam, 2025)
Hospitals, as vital facilities in the healthcare service system, play a crucial role in responding to disaster events, particularly large-scale catastrophic disasters. However, many hospitals in Indonesia still lack an integrated emergency management system that incorporates a community-based approach (Community-Based Disaster Preparedness/CBDP). This study aims to design a catastrophic emergency management model based on CBDP at RSU Grandmed Lubuk Pakam. This research is a qualitative study using an exploratory case study approach. Data collection techniques included in-depth interviews, participatory observations, and document reviews involving key informants such as hospital management, healthcare workers, surrounding community members, and related institutions such as BPBD and PMI. Data were analyzed thematically using the Miles & Huberman model. The results show that although RSU Grandmed has established a disaster management structure, its implementation has not been optimal due to weaknesses in training, coordination, and SOP comprehension. Community involvement in preparedness systems remains minimal, and cross-sectoral coordination has not been formally established.